Concentration of acid detergent fiber, neutral detergent fiber and lignin during solid state fermentation of apple (Malus domestica) derivates - Rodríguez Muela, C.; Rodríguez Ramírez, H. E.; Díaz Plascencia, D.; Bocourt, R.; Arzola Álvarez, C. (Cuban Journal of Agricultural Science, 2017)
In order to evaluate the changes in carbohydrate concentration (CHO) and the consequent loss of dry matter during the solid state fermentation of apple bagasse, two substrate sources were used, which corresponded to two treatments: T1 (100 % apple bagasse), T2 (66.6 % apple bagasse and 33.4 % waste apple). Dry matter, ash, dry matter loss, lactic acid, short chain fatty acids, neutral detergent fiber, acid detergent fiber, lignin and in vitro digestibility of dry matter were measured. A mixed model of SAS was used to study the differences among these variables and substrate sources, days of solid state fermentation and their interaction were established as fixed effects. As random effects, repetitions within T1 and T2 were used. Dry matter of T1 was higher (P <0.05) than that of T2. The percentage of DM increased as the fermentation time passed (3.65 % on day 0, 6.82 % on day 16). It was higher (P<0.05) in T2 (5.23 vs. 4.49 %) than in T1. There was a higher loss of dry matter (P <0.05) from day 0 to 8 in T1 regarding T2 (41.9 vs. 36.9 %, respectively). Acetic acid content was higher in T1 (P <0.05) than in T2, day 0 (29.82 vs. 8.42 mg * g-1 DM) and day 4 (13.40 vs. 1.64 mg * g -1 DM). There were no differences in propionic and butyric acid content. The NDF, ADF and lignin of T1 decreased (P <0.05), while, in T2, they increased (P <0.05) during the time of fermentation. T1 had lower (P <0.05) digestibility than T2, with differences (P <0.05) due to the effect of fermentation day. It was found that, after 96 h of fermentation, 21.94 % of DM was lost in T1 and 17.55 % in T2. At 192 h, DM loss was 41.88 % and 36.92 % in T1 and T2, respectively. It is concluded that, during solid state fermentation, structural carbohydrates are used. Key words: apple bagasse, fermentation, yeast